2003
DOI: 10.1007/s10140-004-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity of plain films in intussusception

Abstract: The aim of this study was to re-evaluate the specificity of plain film findings in intussusception. The plain film findings in 80 cases of proven intussusception were reviewed. Findings documented were: (1) presence or absence of small bowel obstruction, (2) paucity of right lower quadrant gas, (3) presence of an intracolonic mass, (4) presence of a rim or target sign, and (5) presence of the classic triad of intestinal obstruction, intracolonic mass, and paucity of right lower quadrant gas. Intestinal obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 6 publications
2
22
1
1
Order By: Relevance
“…Although many intussusceptions are located in the transverse colon and although a mass is often visible on the supine radiograph, the movement of air into the ascending colon and cecum often outlines the intussusceptum when it is located in the proximal transverse colon or when it has not reached the transverse colon and is located within the ascending colon or cecum, thus expediting subsequent care (Fig 4). Unlike previous investigations that used KUB with upright views (3,8), our results indicate that the KUB plus leftside-down decubitus set is helpful in the diagnosis and care of patients suspected of having intussusception. Initial radiographs provide important information in patients presenting with abdominal findings and important management information in those with intussusception, such as the presence of high-grade small-bowel obstruction and the presence or absence of free air.…”
Section: Pediatric Imaging: Left-side-down Decubitus View For Intussucontrasting
confidence: 73%
See 3 more Smart Citations
“…Although many intussusceptions are located in the transverse colon and although a mass is often visible on the supine radiograph, the movement of air into the ascending colon and cecum often outlines the intussusceptum when it is located in the proximal transverse colon or when it has not reached the transverse colon and is located within the ascending colon or cecum, thus expediting subsequent care (Fig 4). Unlike previous investigations that used KUB with upright views (3,8), our results indicate that the KUB plus leftside-down decubitus set is helpful in the diagnosis and care of patients suspected of having intussusception. Initial radiographs provide important information in patients presenting with abdominal findings and important management information in those with intussusception, such as the presence of high-grade small-bowel obstruction and the presence or absence of free air.…”
Section: Pediatric Imaging: Left-side-down Decubitus View For Intussucontrasting
confidence: 73%
“…Hooker et al with the rate of identification reported by others (Hernandez et al [3] reported 29%; Sargent et al [8] reported 42% with the supine view and 32% with the upright view). This is also in keeping with the data in the 1975 review by Williams (11), which indicates that the abdominal series is expected to depict intussusception in one-third of the cases and to show normal or nonspecific findings in the remaining two-thirds.…”
Section: Pediatric Imaging: Left-side-down Decubitus View For Intussumentioning
confidence: 77%
See 2 more Smart Citations
“…Abdominal X-rays may show dilated gas-filled proximal bowel with paucity of gas distally and multiple air fluid levels but they generally have low sensitivity and specificity for the diagnosis of intussusception as a quarter of intussusception cases have a normal abdominal radiograph. [10] The well established imaging modality for the diagnosis of intussusception is an abdominal ultrasonography. It is quite sensitive, specific, reliable and inexpensive tool for diagnosing intussusception and can also help in identification of pathological lead points.…”
Section: Discussionmentioning
confidence: 99%